RANCANG BANGUN SISTEM PENGENDALI SUHU DAN KELEMBAPAN PADA GUDANG PENYIMPANAN KOMPONEN PESAWAT TERBANG - Ahmad Ridho; Akhmad Musafa (MAESTRO, 2022)
In this final project, a temperature and humidity control system for aircraft component storage has been designed using a PID controller and ON/OFF controller. This system is designed so that the warehouse component storage temperature of aircraft components, especially the avionic component (aviation electronic) which has a storage requirement at a temperature of 16-26 °C and humidity at 40-65% maintained at the reference temperature, so that the quality and state of components stored in the warehouse will stay awake his life span and abilities. The control system that was designed consisted of 1 unit 12VDC 10A power supply, 1 unit DC-DC Converter, 1 unit Arduino Uno microcontroller board, 4 DHT22 sensors, 1 unit 2 Channel Relay, 1 unit 180 ° servo motor, and 1 unit dehumidifier. The reference temperature is set at 24 °C and the reference humidity at 60%. The control system consists of a PID controller to control temperature and an ON / OFF controller to control humidity. When the warehouse room is fed with a central AC (air conditioner) flow, the sensor will read the temperature and humidity of the room. The sensor readings will be sent to Arduino to be compared with a predetermined set point. The temperature error value will be processed by the PID with an output control signal in the form of a PWM signal (50Hz) to control the rotation of the servo motor used to open or close the central AC flow. While the humidity error signal will be processed by the ON / OFF controller with an output signal in the form of an ON or OFF state for the relay that is used as a switch for the dehumidifier. The test results with the PID parameter values ​​Kp=75, Ki=40, and K =45 obtained by the heuristic method produces a good system response. The temperature can be controlled between 24 °C - 26 °C and humidity can be lowered when it is above 60%.